Improvements in Safety Outcomes Following Brief Healthcare-Based Intimate Partner Violence Interventions among Women Who Screen Positive for Intimate Partner Violence-Related Traumatic Brain Injuries - Michelle M. Pebole; Brigitta M. Beck; Colin T. Mahoney; Katherine M. Iverson (Brain Sciences)
Background: Traumatic brain injuries (TBIs) are a common consequence of experiencing intimate partner violence (IPV). IPV-related TBI contributes to adverse health outcomes among women, but it is unknown whether a history of IPV-related TBI negatively impacts safety outcomes following healthcare-based interventions for IPV. Methods: Using data from a larger randomized clinical trial, we explored the impact of IPV-related TBI status on safety-related outcomes in two healthcare-based IPV interventions. At baseline, 35% (n = 21) of the sample screened positive for IPV-related TBI history. We used repeated measures ANOVAs to examine differences in safety outcomes at post-treatment and 1-month follow-up based on treatment condition and IPV-related TBI status. Results: Significant interaction effects were found for safety outcomes, such that women with IPV-related TBI history experienced larger reductions in the frequency of physical IPV and similar reductions in sexual IPV across both treatment conditions compared to women without IPV-TBI (F(2, 102) = 10.88, p < 0.001; F(2, 98) = 3.93, p = 0.036). Conclusions: Findings suggest that brief healthcare-based IPV interventions may result in improvements in safety outcomes for women with a history of IPV-TBI. This highlights the continued need for implementation of promising IPV-focused interventions to promote safety and protect women from experiencing further IPV.